Outcomes of EUS-FNA in patients receiving antithrombotic therapy - Polmanee, Petcharee; Hara, Kazuo; Mizuno, Nobumasa; Hijioka, Susumu; Kuwahara, Takamichi; Okuno, Nozomi; Iwaya, Hiromichi; Tajika, Masahiro; Tanaka, Tsutomu; Ishihara, Makoto; Hirayama, Yutaka; Ohnishi, Sachiyo; Toriyama, Kazuhiro; Bhanthomkomol, Patommatat; Ito, Ayako; Kuraoka, Naosuke; Matsumoto, Shinpei; Niwa, Yasumasa (Endoscopy International Open, 2019)
Background and study aims To investigate bleeding risk and thromboembolic risk in patients receiving antithrombotic therapy who underwent endoscopic ultrasound-guided fine-needls aspiration (EUS-FNA). Patients and methods A single-center retrospective study of 908 consecutive patients undergoing EUS-FNA for pancreatic and non-pancreatic lesions patients between March 2013 and March 2017 was performed. Antithrombotic management was classified into three groups: continuous, discontinuation, and heparin replacement. Results A total of 114 patients (12.6 %) were on antithrombotic drugs and 794 (84.6 %) were not. There were six cases of significant bleeding (0.7 %) four in the antithrombotic group (0.4 %) and two (0.2 %) in the non-antithrombotic group, (odds ratio, 9.59; 95 % confidence interval, 2.12 – 43.1; P = 0.006). Of the four cases in the antithrombotic group, two were on continuous treatment, one was on discontinuation treatment and one was on heparin replacement. All cases of non-significant bleeding occurred in the non-antithrombotic group (3 peri-tumoral hematomas, 1 submucosal hematoma, and 1 intraluminal bleed). The sole thromboembolic event (0.9 %) was a cerebral infarction in the antithrombotic group in a patient on thienopyridine who switched to aspirin before the procedure. Conclusions There was a slight increase in risk of bleeding in patients receiving antithrombotic therapy especially postoperative bleeding; however, there were no cases of severe bleeding was seen and only one case of cerebral infarction which occurred in a high-risk thromboembolic patients. We concluded that EUS-FNA in a safe procedure for patients on antithrombotics, even when antithrombotic therapy is not discontinued during EUS-FNA.